Patient-Derived Extracellular Vesicles Proteins as New Biomarkers in Multiple Myeloma - A Real-World Study - Ferreira, Bruna Velosa; Carneiro, Emilie Arnault; Pestana, Carolina; Barahona, Filipa; Caetano, Joana; Lopes, Raquel; Lúcio, Paulo; Neves, Manuel; Beck, Hans Christian; Carvalho, Ana Sofia; Matthiesen, Rune; Costa-Silva, Bruno; et al. (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is a hematological malignancy of clonal antibody-secreting plasma-cells (PC). MM diagnosis and risk stratification rely on bone marrow (BM) biopsy, an invasive procedure prone to sample bias. Liquid biopsies, such as extracellular vesicles (EV) in peripheral blood (PB), hold promise as new minimally invasive tools. Real-world studies analyzing patient-derived EV proteome are rare. Here, we characterized small EV protein content from PB and BM samples in a cohort of 102 monoclonal gammopathies patients routinely followed in the clinic and 223 PB and 111 BM samples were included. We investigated whether EV protein and particle concentration could predict MM patient prognosis. We found that high EV protein/particle ratio, or EV cargo > 0.6 µg/108 particles is related to poorer survival and immune dysfunction. These results were supported at protein level by mass spectrometry. We report a set of PB EV-proteins (PDIA3, C4BPA, BTN1A1 and TNFSF13) with new biomarker potential for myeloma patient outcomes. The high proteomic similarity between PB and BM matched pairs is supporting the use of circulating EV as counterpart of BM EV proteome. Overall, we found that EV protein content is related to patient outcomes, such as survival, immune dysfunction, and possibly treatment response.